PENDAFTARAN HAK MEREK SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP INDUSTRI UMKM - Irma Abidahsari; Tegar Hartantha Pratama; Margaretha Andini Oktavina; Jason Sebastian Tunru (PROSIDING SERINA, 2021)
The activities of micro, small and medium enterprises as productive businesses are growing rapidly which is shown in the large number of MSME actors in Indonesia. Brands are important in the running of Micro, Small and Medium Enterprises (MSMEs). This is motivated by the fact that there are still at least MSME actors who register their trademark rights legally, compared to those who do not register their trademark rights. The author in this paper aims to find out related to MSME Brand Rights, and can find out the existing Legal Protection of MSME Brand Rights. The method taken by the author here is a descriptive qualitative method. At the point of the research results, the author takes 2 cases of trademark rights disputes that have occurred in Indonesia and the discussion and conclusion that brand rights as the identity of UMKM products with a lack of awareness of UMKM actors to register trademark rights legally which is associated with the example of Ruben Onsu's trademark lawsuit case to PT Ayam Geprek Benny Sujono "I AM GEPREK BENSU" and also the existence of Legal Protection for Trademark Rights Repressive and Preventive Efforts if there is a violation of MSME Brand Rights and it is important here that legal protection is only applied to registered MSME Brand Rights. Thus, the registration of trademark rights by MSME actors to the Directorate General of Intellectual Property Rights and the Ministry of Law and Human Rights will protect and prevent disputes over trademark rights in the future.Kegiatan usaha mikro, kecil dan menengah (UMKM) sebagai usaha produktif yang berkembang pesat yang ditunjukan pada banyaknya pelaku UMKM di Indonesia. Merek menjadi penting dalam berlangsungnya Usaha Mikro Kecil dan Menengah (UMKM). Dilatarbelakangi dengan masih sedikitnya Pelaku UMKM yang mendaftarkan Hak Mereknya secara sah, dibanding dengan yang tidak mendaftarkan hak mereknya. Penulis dalam Makalah ini bertujuan untuk mengetahui terkait Hak Merek UMKM, serta dapat mengetahui Perlindungan Hukum Hak Merek UMKM yang telah ada. Metode yang diambil Penulis disini ialah metode kualitatif deskriptif. Pada poin hasil penelitian penulis mengambil 2 kasus sengketa Hak Merek yang pernah terjadi di Indonesia serta bahasan serta simpulan bahwasannya Hak merek sebagai identitas Produk UMKM dengan kurangnya kesadaran Pelaku UMKM untuk mendaftarkan Hak Merek secara sah yang dikaitkan dengan contoh Kasus Gugatan Hak Merek Ruben Onsu kepada PT Ayam Geprek Benny Sujono “I AM GEPREK BENSU” dan juga telah adanya Perlindungan Hukum Hak Merek Upaya Represif dan Preventif bila adanya pelanggaran Hak Merek UMKM dan penting disini bahwa perlindungan hukum hanya diberlakukan pada Hak Merek UMKM yang telah didaftarkan. Maka, dengan didaftarkannya Hak Merek oleh Pelaku UMKM kepada Dikjen HAKI dan Depkumham akan menjadi perlindungan dan mencegah timbulnya sengketa hak merek tersebut dimasa depan.